(untitled) (Raparin Journal of Humanities (RJH), 2019)
Karl Raimund Popper is one of the influential and prominent philosophers in the 20th century, who had a crucial role in the natural and social sciences. Whatever he discussed was the subject to study and engaged many researchers and intellectuals in it. This thesis is another paper which shows an effective and a wide range of Popper’s philosophy field. Popper`s criticism of Historicism is one of his characteristics that he is known for. In addition, it can be said that his two books entitled the (The poverty of Historicism, and The Open Society and It`s Enemies) have been dedicated to this purpose. In this thesis (Criticism of Historicism by Karl Popper), the focus is on Popper`s criticism of Historicism and it attempts to display his perspective on this issue objectively.